2020
DOI: 10.35609/jber.2020.5.1(5)
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Perspective on Telecom Mobile Data Traffic

Abstract: Objective – The global industry is transforming into a digital world, evidenced by digital transformation performed by almost all of the industry sectors. One of the digital drivers is the support of connectivity provided by the telecommunication industry. The increasing mobile subscribers, along with the growth of mobile data traffic, is the sign of digital transformation itself. However, the rise of OTT (Over the Top) service providers tends to acquire the revenue share of the current telecom industry, seein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
0
0
Order By: Relevance
“…The Levene test indicates the similarity of variances (sig > 0.05). ANOVA (sig = 0.004) is also carried out, confirming the null hypothesis's rejection [66]. However, which are the statistically different means between all P38 groups?…”
Section: Overall Samplesupporting
confidence: 52%
“…The Levene test indicates the similarity of variances (sig > 0.05). ANOVA (sig = 0.004) is also carried out, confirming the null hypothesis's rejection [66]. However, which are the statistically different means between all P38 groups?…”
Section: Overall Samplesupporting
confidence: 52%
“…All students studying at public tertiary institutions must have access to the internet that is optimized in terms of availability and speed by the educational institution and the country as a whole. This result was supported by Hendrawan, Nugroho, and Permana [10] who found that the Philippines was one of the countries with the highest rates of social media use globally. Thus, because of the rising demand for internet connections, people in the 21st century are 83.46%…”
Section: Students' Number Of Years Of Internet Usagementioning
confidence: 66%